Caracterização mineralógica e microestrutural visando a previsibilidade de processo de minério de ferro - Bolivar Bruno Otony Duarte (2021)
Mineralogical characterization is of high importance due to the complexity of the different types of ores that make up a reserve. This study focuses on morphological characteristics and particles microstructures. The following methods were used: reflected light microscope, X-ray diffraction, quantitative chemical analysis and the scanning electron microscope (SEM) with EDS microanalysis (QEMSCAN), aiming to confirm the results obtained. This study was applied to three lithologies presenting different degrees of difficulties and representing the ore to be fed in a short and medium term future. For theprocess predictability, the following microstructural characteristics of the particles were analyzed: morphology, mineralogical compositions, and liberation and grain fabric. The conclusive results indicate that in the crushing stage, predictability emphasizes the positive performance of the nine samples that presented high porosity, so that the microcracks of the samples under analysis favor the crushing process. The grinding stage presented two samples with positive performance and intermediate performance in the other samples. The stages of desliming and flotation indicated a sample requiring extra attention in the process due to a high percentage of contaminants such as goethite, phyllosilicate and gibbsite. This occurrence requires greater attention and control in the blend process. The other samples presented intermediate performance, due to the presence of the contaminants goethite and gibbsite, that are present in lower percentage. A conclusive aspect is the finding that the presence of ultrafme iron minerals particles, or contaminants with granulometry above the standards, compromises the process.